Incidence of factor VIII inhibitory antibodies in patients with hemophilia A seen at HEMOCE, Ceará, Brazil - Rosineide A Carvalho; Paulo Henrique da Silva; Railson Henneberg
ABSTRACT Introduction: Hemophilia A is an inherited disease caused by a deficiency of factor VIII, which results from a genetic inheritance located on the X chromosome. During treatment of patients with this disorder, factor VIII inhibitors may be present, which are primarily antibodies type immunoglobulin G (IgG), and interfere with the activation of factor VIII. Objectives: The present study aims to investigate and quantify the presence of antibodies against factor VIII:C in patients with hemophilia A, treated at the Ceará Hematology Center (HEMOCE). Material and methods: Screening for the inhibitor against factor VIII was performed according to the original Bethesda method or the Nijmegen modified assay. Results: One hundred eighty-four patients with hemophilia A were evaluated, from November 2012 to February 2015. From the patients evaluated, 149 (80.98%) showed no inhibitor presence, while in 35 patients (19.02%) the presence of the inhibitor was detected. Among inhibitor carriers, most hemophilia patients had high titers of the inhibitor (57.2%). Conclusion: The high incidence of factor VIII inhibitor in the study population can be explained by the type of treatment used at HEMOCE, which is based on the factor VIII in its recombinant form. The results should be evaluated carefully, so that the treatment and monitoring of these patients are conducted in the safest way possible.